Student's Strategy In Learning Vocabulary at English Department of STKIP PGRI - Nanik Sulastri (JURNAL ARBITRER, 2019)
This research was conducted to: (1) To examine the vocabulary learning strategies (2) To find out  the most and the least vocabulary learning strategies that used by the (3) To analyze the factors affect the students in choosing the vocabulary learning strategy of English Language Education Program at STKIP PGRI Sumbar. The research applied a descriptive research; the population of this research was the eighth-semester students in academic year 2017/2018. The samples of this research were 49 students chosen by using total sampling technique. The data were analyzed by using descriptive analysis and used Power score and estimate stage for Academic vocabulary. The research result showed that (1) the students’ vocabulary proficiency; it was classified as late gradation. It can be said that most of the students are in late gradation in percentage 60.71% and only less students who get early gradation. (2) the most learning strategy mostly used by the students was Consolidation learning strategies in learning vocabulary on percentage 40,81% students . (3) Some factors affect the choosing of vocabulary language learning strategies were found. It was found that the late gradation students chose Memory learning strategies as their strategy in learning vocabulary because of believe, motivation and learning experience. It can be concluded that the students' learning strategy affected their proficiency in vocabulary.